A label-free LC/MS-based enzymatic activity assay for the detection of PDE5A inhibitors - Ma, Yufeng; Zhang, Fengsen; Zhong, Yijing; Huang, Yongchun; Yixizhuoma,; Jia, Qiangqiang; Zhang, Shoude (Frontiers in Chemistry, 2023)
Phosphodiesterase type 5 (PDE5), a cyclic nucleotide phosphodiesterase, controls the duration of the cyclic guanosine monophosphate (cGMP) signal by hydrolyzing cGMP to GMP. Inhibiting the activity of PDE5A has proven to be an effective strategy for treating pulmonary arterial hypertension and erectile dysfunction. Current enzymatic activity assay methods for PDE5A mainly use fluorescent or isotope-labeled substrates, which are expensive and inconvenient. Here, we developed an LC/MS-based enzymatic activity assay for PDE5A without labeling, which detects the enzymatic activity of PDE5A by quantifying the substrate cGMP and product GMP at a concentration of 100 nM. The accuracy of this method was verified by a fluorescently labeled substrate. Moreover, a new inhibitor of PDE5A was identified by this method and virtual screening. It inhibited PDE5A with an IC50 value of 870 nM. Overall, the proposed strategy provides a new method for screening PDE5A inhibitors.